'I am assumed to be someone who doesn't have to deal with diversity': countering the denial of diversity in rural teacher education. (2nd October 2017) - Anthony-Stevens, Vanessa; Gehlken, Emily; Jones, Chelsea; Day, Sheriden; Gussenhoven, Sarah
Abstract: In this article, the researchers examine the role of diversity in a pre-service teacher education programme in a predominately white public university in the United States rural north-west region. Using ethnographic and autoethnographic methods, one professor and four pre-service education students from across early childhood, primary and secondary education examine how issues of diversity are addressed in coursework and practicum teaching experiences. Findings reveal a pervasive discourse of denying diversity in the rural landscape, limited programmatic engagement with diversity as a body of knowledge and skill set for teaching and course interactions which thwart teachers' abilities to address inequity in dynamic communities, locally and globally. We counter these limitations by proposing rural universities engage with pre-service teachers in reflective dialogue as critical stakeholders in (re)conceptualizing rurality as diverse, and as co-partners in mapping increased attention to culturally relevant education as an applied stance in a dynamic and changing democracy.